Sistem Semi Otomasi pada Proses Tinning Pin Lampu di PT. Excelitas Technologies Batam - Diono Diono; Gindo Leonard Manahan Simanjuntak; Handri Toar; Muhammad Syafei Gozali; Adlian Jefiza (JURNAL INTEGRASI, 2022)
The tinning process is the process of coating a thin sheet of wrought iron or steel with tin and the resulting product is known as tinplate. The tinning process at PT. Excelitas Technologies Batam is done by clamping the lamp using your finger and then dipping it into flux and molten tin repeatedly until the lamp pin is evenly coated with tin which is done manually and is very dangerous for workers. Therefore, we need a Semi Automation System for the PLC-based Lamp Tinning Process. The method used is the use of a timer in the PLC-based flux dyeing and tining process. The tool testing process is carried out on 10 pcs lamp pins which are immersed 2 times in the flux and tinning process. The result of this research is that the cycle time loading / unloading of the lamp pin tinning process is reduced from 14.4 seconds to 11 seconds.